Workshop and Mentoring of Product Preservation and Marketing For Food and Beverage SMEs in Gresik Regency - Nyoman Sri Widari; Badriyah Badriyah; Dedy Kunhadi Kunhadi (OJS Universitas Muhammadiyah Gresik, 2019)
Small and Medium Enterprises (SMEs) have an important role in the economy of a country, including in Indonesia. Although SMEs have contributed to economic growth, in their development there have been various problems. The problem faced by SMEs in Gresik Regency is that they do not understand the use of preservatives food and beverage that are safe for health and limited market access. In solving the problems faced by these SMEs, the community service team transferred knowledge and technology through workshops and mentoring. Workshop material includes methods of processing and preserving food, types of natural preservatives, and ways to promote, market, and sell products through online marketing media (e-commerce). While mentoring was carried out after the workshop was completed. With the completion of community service activities, it is expected that SMEs can increase product durability and product quality by using natural preservatives that are safe for health, and SMEs are able to run and manage e-commerce applications that have been developed.